Self-confidence Level among Intern Dentists in Performing Endodontic Treatment Procedures in Nepal - Chakradhar, A.; Humagain, M.; Acharya, N.; Pradhan, S.; Poudel, P. (Kathmandu University Medical Journal, 2021)
Background Endodontics is considered as one of the most difficult and stressful disciplines in dentistry. This might be due to the complex anatomical variations, recent advances in equipment, technology, materials and lack of self-confidence. Objective To determine the self-confidence level among the intern dentists in performing endodontic procedures from six different colleges of Kathmandu University, Nepal. Method A descriptive cross-sectional study was conducted among 145 intern dentists. The online questionnaire regarding confidence level (5 point Likert scale) in different endodontic procedures and difficulty level (easy, ok and difficult) with respect to teeth was distributed. For descriptive purpose, frequency and percentage for each response were calculated. Result Dental interns were confident in performing majority of the normal endodontic procedures, however, they showed less confidence in performing difficult steps like rubber dam application for anterior (74, 51%) and posterior tooth (91, 62.7%), use of electronic apex locator (89, 61.4%), using rotary files (114, 78.6%), management of flare-ups (86, 59.4%), assessment of quality of post-endodontic treatment (85, 58.5%), recall periods (75, 51.6%) and performing post and core (82, 56.6%). Likewise, upper first molars (84, 57.9%) and second molars (104, 71.7%) were found to be the most difficult teeth to treat. Conclusion It can be concluded that majority of the dental interns were confident in performing basic endodontic procedures, however, they were found to have low confidence in performing difficult steps. Further training and exposure should be incorporated to increase their confidence level.